Marketplace Responsibility for the Trade in Counterfeit Formula Milk from the Perspective of MUI FATWA NO. I/MUNAS VII/MUI/5/2005 Concerning Intellectual Property Rights - Audi Mutia Adrivia Nasution; Rahmad Efendi (LP2M IAIN Palopo, 2026)
Marketplaces make it easier for consumers to search and compare products to be purchased on the marketplace platform. Consumers have the opportunity to get products at relatively low prices through various offers listed in the product description. However, it is undeniable that this convenience raises issues regarding product authenticity, especially if the product is sold at a low price from an unauthorized store, one of which is the trade of counterfeit formula milk on Shopee and Tokopedia. This study aims to determine and analyze what trademark violations are, and how the marketplace's responsibility is towards the trade of counterfeit formula milk products from the perspective of the MUI fatwa Number I/MUNAS VII/MUI/5/2005. This type of research uses normative juridical with a descriptive analytical research nature, the data source used is secondary data as the main source. Data were collected through library research. The documents collected include laws and regulations, the MUI Fatwa Number I/MUNAS VII/MUI/5/2005, and include various literature related to the research such as books, relevant scientific journals, and other academic references that support the research analysis. The research results show that there are trademark violations committed by individuals with bad intentions and are not responsible for their actions, namely piracy, counterfeiting, and imitation of brand labels. And the marketplace's responsibility for the trade in counterfeit formula milk covers several aspects, namely: quality control, safety, and the validity of product information.